Pendampingan UMKM Berbasis Literasi Keuangan di Desa Simpang Sender Timur, Buay Pematang Ribu Ranau Tengah - Mutmainah Juniawati; Husnah Lutfiah; Varisya Amelia (Universitas Negeri Gorontalo, 2026)
Lack of financial literacy in terms of financial management skills has an impact on Micro, Small, and Medium Enterprises (MSMEs) in Simpang Sender Timur Village located in Buay Pematang Ribu Ranau Tengah District, Ogan Komering Ulu Selatan Regency, which is 1 of 58 underdeveloped villages in South Sumatra in improving and maintaining the stability of their businesses, and Micro, Small, and Medium Enterprises (MSMEs) in Simpang Sender Village have difficulty in selling palm sugar and processed coffee powder. The purpose of this Community Service (PKM) activity is to improve understanding of financial literacy within the MSME actor group in Simpang Sender Timur Village located in Buay Pematang Ribu Ranau Tengah District, Ogan Komering Ulu Selatan Regency, so that MSME actors can be more effective in managing their financial aspects and providing solutions related to obstacles in developing their MSMEs. This Community Service (PKM) method is carried out in four stages consisting of a survey, mentoring on financial literacy in the form of basic financial reports which also include the practice of preparing simple financial reports, and evaluation (pre-test and post-test). The results of the activity show that before the mentoring on financial literacy was held, MSME actors in Simpang Sender Timur Village located in Buay Pematang Ribu Ranau Tengah District, South Ogan Komering Ulu Regency had a low level of literacy, some MSME actors did not have financial records, but after the mentoring activity for MSME actors in Simpang Sender Timur Village, their financial literacy increased to 24% although it has not increased significantly due to the short time in mentoring, MSME actors in Simpang Sender Timur Village have had an awareness of the need for high financial literacy in maintaining the stability and sustainability of their businesses